Increased serum concentrations of soluble CD95/Fas and caspase 1/ICE in patients with acute angina. Issue 2 (16th January 2004) - Ankersmit, H J; Weber, T; Auer, J; Roth, G; Brunner, M; Kvas, E; Moser, B; Spreitzer, S; Lassnig, E; Maurer, E; Hartl, P; Wolner, E; et al.
Abstract : Objectives: To investigate the expression of death inducing receptors in the sera of patients with stable and unstable angina. Design: 80 consecutive patients with stable (n = 40) or unstable (n = 40) angina pectoris were studied. Serum concentrations of soluble CD95 (sCD95), soluble CD95 ligand (sCD95L; CD178), tumour necrosis factor (TNF) α, soluble TNFα receptor type 1 (sTNFR1), and interleukin 1β converting enzyme (ICE; caspase 1) were measured by enzyme linked immunosorbent assay (ELISA). Results: Significant increases in the concentrations of sCD95 and ICE (p < 0.001 and p < 0.023, respectively) were found in the serum from patients with unstable angina relative to those with stable angina. There were no significant differences in the concentrations of sCD95L, TNF α, and sTNFR1 between the groups. Conclusions: These data provide the first evidence that sCD95 and ICE are important serological markers that may help to discriminate between stable and unstable angina. This observation may warrant further clinical study to elucidate the clinical impact of sCD95 and ICE in acute coronary syndromes.